2007
DOI: 10.1002/cmmi.128
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of antigen‐induced arthritis with a new, folate receptor‐targeted contrast agent

Abstract: The purpose of this study was to investigate if the new folate receptor-targeted Gd-chelate P866 may enhance immune-mediated arthritis. A monoarthritis was induced in the right knee of 15 Sprague-Dawley rats. MR imaging of both knees was performed at 2 T before and up to 2 h and 24 h after injection (p.i.) of P866 (n = 3 dose finding study and n = 6, 0.02 mmol Gd/kg), the non-FR targeted P866 analog P1001 (n = 3 at 24 h after P866-administration, 0.02 mmol Gd/kg) or Gd-DOTA (n = 6, 0.1 mmol Gd/kg). Pulse seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…This study’s group and others have reported that stem cells, labeled with clinically approved gadolinium chelates, can be tracked in arthritic joints [64,65]. Thus, gadolinium labeling would represent a potential alternative to ferumoxytol labeling.…”
Section: Discussionmentioning
confidence: 99%
“…This study’s group and others have reported that stem cells, labeled with clinically approved gadolinium chelates, can be tracked in arthritic joints [64,65]. Thus, gadolinium labeling would represent a potential alternative to ferumoxytol labeling.…”
Section: Discussionmentioning
confidence: 99%
“…In the pilot study, we tried to apply conventional postcontrast T1 MR images and compared the enhancement ratio of the FR-positive and -negative tumors at various time points (4,8,12, and 24 h...) after contrast injection, as other authors did in previous receptor-targeted MR studies [15,30]. However, we found that it was difficult to get exactly the same imaging plane of the tumors once we re-arranged the mouse position and the baseline MR signal intensity fluctuated at various time points due to MR unit internal variability.…”
Section: Discussionmentioning
confidence: 99%
“…In previous receptor-targeted magnetic resonance (MR) imaging studies, authors usually compared the contrast enhancement ratio between the receptor-positive and the -negative tumors at various time points after contrast injection, and showed that the receptor-positive tumors had higher enhancement ratios and longer enhancement durations [12][13][14][15][16][17][18]. However, it is sometimes hard to scan exactly the same cross-sectional area before, and at different time points after contrast injection; thus, it is hard to get unbiased hemodynamic information from a certain portion of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the targeting ligands that have been examined for cancer detection is presented in Table 3 [21, 27, 5254, 86104]. Ideally, the targeting ligand should bind exclusively to a receptor on a specific type of cancer cell.…”
Section: Delivery and Targeting Of Inorganic Nanoparticlesmentioning
confidence: 99%